Design alternate epoxy-reduced graphene oxide/epoxy-zinc multilayer coatings for achieving long-term corrosion resistance for Cu. (15th January 2020) - Ge, Tianhao; Zhao, Wenjie; Wu, Xuedong; Wu, Yangmin; Shen, Lu; Ci, Xiaojing; He, Yanlin
Abstract: To make good use of the barrier effect of graphene nanosheets and to reduce the uneven dispersion of zinc particles caused by its sedimentation, coating with alternate structure containing rGO was developed to provide Cu a long-term corrosion protection. Ionic liquid was used to obtain a better dispersion of rGO in solvent, which was proved by TEM, SPM images and sedimentation experiment. The enhanced long-term anti-corrosion protection of alternate coating was revealed by electrochemical tests. OCP and EIS results showed enhanced barrier performance of epoxy-G compared with epoxy and improved sacrificial anode protection of epoxy-Zn-G compared with epoxy-Zn. Tidal range-corrosion simulation test was also performed to show that the alternate coating can stick on copper substrate without peeling off even in harsh corrosive environment for 432 h. Furthermore, EIS, XRD, and XPS spectra together proved that the excellent anti-corrosion property of alternate coating was originated from the combination of sacrificial anode protection provided by zinc-rich-epoxy layer with barrier protection provided by rGO-doping-epoxy layer. This combination makes it reality to protect copper substrate from corrosion for longer time immersion in 3.5 wt% NaCl solution compared with epoxy-Zn-G. Graphical abstract: Image 1 Highlights: An alternate epoxy-reduced graphene oxide/epoxy-Zinc multilayer coating is designed for enhancing anticorrosion. The alternate structure can achieve an analogous sustained release effect of zinc particles. The coating with alternate structure achieves longer protection than single structure in 3.5 wt% NaCl solution. The coating with alternate structure shows strong adhesion strength in acidic environment for 432 h.